Pemberian Edukasi dan Keterampilan tentang Pijat laktasi untuk Meningkatkan Produski Asi pada Ibu Menyusui - Musni Musni; Desi Heriyana; St. Malka; Mutmainnah Mutmainnah; Irawati Irawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Breast milk (ASI) is a natural nutrition for babies with the most appropriate nutritional content for optimal growth. Decreased breast milk production in breastfeeding mothers is one of the causes of the failure to provide exclusive breastfeeding for the first 0-6 months. Some mothers experience difficulties and failures in breastfeeding because breast milk has not come out, little breast milk or sore nipples. Lactation massage is one method of painless breast care that can stimulate the strength of the breast muscles to increase breast milk production. The purpose of this service is to provide education and skills to mothers about the benefits of lactation massage and how to do lactation massage to increase breast milk production. The service method used is a lecture on the benefits of lactation massage and practice on how to do lactation massage. The results of the evaluation of the implementation before the counseling were given, the knowledge category was sufficient (58.8%) and after the counseling was given it became (88.2%), meaning that the activities carried out could increase the knowledge and skills of mothers.